Penerapan Game To Be Detective Untuk Menyusun Kalimat Tanya Dalam Pembelajaran Bahasa Arab/Application of the Game To Be Detective to Compose Interrogative Sentences in Learning Arabic - Puti Rindang Sari; Muassomah Muassomah; Slamet Daroini; Idrus Muchsin Bin Agil (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2023)
Learning Arabic with the game To Be Detective is the newest learning method at MTsN 7 Malang. This study used descriptive qualitative method. Data collection techniques used were participant observation, in-depth interviews and documentation. Observation of the process of learning Arabic with the game To Be Detective. In-depth interviews were conducted by interviewing Arabic teachers and students of class VIII MTsN 7 Malang. The results of the study show that 1) There are 6 steps in the process of learning Arabic with games To Be Detective at MTsN 7 Malang, namely material explanation, group division, explanation of games To Be detective, constructing interrogative sentences, answering interrogative sentences, presenting work results and evaluating. 2) learning by using games to be detective can increase the enthusiasm and motivation of student learning because these games are very interesting for the student learning process, in addition to training perseverance, skills, cooperation for students. Abstrak: Pembelajaran bahasa Arab dengan permainan To Be Detective merupakan metode pembelajaran terbaru di MTsN 7 Malang. Penelitian ini menggunakan metode kualitatif deskriptif. Teknik pengumpulan data yang digunakan adalah observasi partisipan, wawancara mendalam dan dokumentasi. Observasi proses pembelajaran bahasa Arab dengan permainan To Be Detective. Wawancara mendalam dilakukan dengan mewawancarai guru bahasa Arab dan siswa kelas VIII MTsN 7 Malang. Hasil penelitian menunjukkan bahwa 1) Terdapat 6 langkah dalam proses pembelajaran bahasa Arab dengan game To Be Detective di MTsN 7 Malang, yaitu penjelasan materi, pembagian kelompok, penjelasan game To Be detective, menyusun kalimat tanya, menjawab kalimat tanya , mempresentasikan hasil kerja dan evaluasi. 2) pembelajaran dengan menggunakan permainan detektif dapat meningkatkan semangat dan motivasi belajar siswa karena permainan ini sangat menarik bagi proses belajar siswa, selain melatih ketekunan, keterampilan, kerjasama bagi siswa.